Identifikasi Gugus Fungsi Limbah Minyak Trafo yang Digunakan sebagai Minyak Obat Luka Menggunakan FTIR - Hidayanti, Nurul; Rahmawati, Rahmawati; Maryam, St. (PHARMACY UMI JOURNAL SYSTEM, 2023)
Communities living close to PLN empirically use waste transformer oil as a medicine for wounds such as cuts or cuts and burns such as being exposed to oil or hot cooking utensils. Transformer oil has the main function as an insulating medium and as a coolant. This study aims to determine the chemical components contained in transformer oil waste by using FTIR. The results of research on transformer oil waste using the FTIR method showed that there were carboxyl functional groups, amide groups, aromatic rings, nitro groups and alkyl groups.